Rezerwy celowe w hiszpańskim systemie bankowym - Orzeszko, Teresa (Specific provisions in the Spanish banking system, 2005)
Specific provisions occupy an important position among various factors which determine safety and stability of credit granting institutions. In spite of the fact that they constitute a traditional, widely known and applied instrument used to eliminate risk, the principles of their functioning have not yet been harmonized in an international scale, so as a consequence they differ in many respects with regard to particular banking systems. Spain is one of these countries where specific provisions are subject to detailed regulations of banking accountancy, announced by the central bank, which also thoroughly and regularly controls the correctness of their application by credit granting institutions, and this factor limits, to a great extent, freedom of their functioning with regard to their influence on the level and structure of such provisions. Despite an extensive formalization of specific provisions, another of their characteristic features is the fact that they are not the only type of provisions created by credit granting institutions in order to neutralize negative effects of credit risk, but only an element of the provisions’ system related to credit risk, which also includes general provisions, statistical ones (since 2000) and the state risk provisions. One more property of specific provisions in the discussed country is their cyclical nature, which manifests itself in the fact that the value of provisions decreases significantly in the period of economic growth and increases in the recession phase. It is also characteristic for Spain that specific provisions, created by credit granting institutions to the level of the required minimum, are regarded as the cost of revenues.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1091, s. 60-72